Genetic and environmental influences on early literacy skills across school grade contexts. Issue 5 (6th August 2016) - Haughbrook, Rasheda; Hart, Sara A.; Schatschneider, Christopher; Taylor, Jeanette
Abstract: Recent research suggests that the etiology of reading achievement can differ across environmental contexts. In the US, schools are commonly assigned grades (e.g. 'A', 'B') often interpreted to indicate school quality. This study explored differences in the etiology of early literacy skills for students based on these school grades. Participants included twins drawn from the Florida Twin Project on Reading ( n = 1313 pairs) aged 4 to 10 years during the 2006–07 school year. Early literacy skills were assessed with DIBELS subtests: Oral Reading Fluency (ORF), Nonsense Word Fluency (NWF), Initial Sound Fluency (ISF), Letter Naming Fluency (LNF), and Phoneme Segmentation Fluency (PSF). School grade data were retrieved from the Florida Department of Education. Multi‐group analyses were conducted separately for subsamples defined by 'A' or 'non‐A' schools, controlling for school‐level socioeconomic status. Results indicated significant etiological differences on pre‐reading skills (ISF, LNF, and PSF), but not word‐level reading skills (ORF and NWF). There was a consistent trend of greater environmental influences on pre‐reading skills in non‐A schools, arguably representing 'poorer' environmental contexts than the A schools. Importantly, this is the case outside of resources linked with school‐level SES, indicating that something about the direct environment on pre‐reading skills in the non‐A school context is more variable than for A schools. Abstract : The grade a school receives is often used as a proxy for school quality. Our study finds that, across school grade contexts the etiology for early literacy skills differs. More specifically, pre‐word reading skills appear to be influenced by more genetic factors in higher‐graded schools, while environmental factors are more influential in lower‐graded schools.